PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT KUMALA INDONESIA SHIPYARD DI KOTA BATAM - Fernanda, Muhammad; Wasiman (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine the effect of compensation and organizational culture on performance on employee performance at PT Kumala Indonesia Shipyard in Batam City. This study usesquantitative methods. The data is obtained by using numbers and the analysis is using statistical techniques. The data taken for this study were 100 employees at PT Kumala Indonesia Shipyard in Batam City. Data collection was done by using a questionnaire. The data analysis technique used is the analysis of grouping the data based on the variables and types of respondents. This study concludes that compensation and organizational culture affect motivation, compensation and organizational culture affect employee performance, motivation affects employee performance and compensation and organizational culture affects employee performance through motivation as an intervention variable.